Thermal Fouling of Heat Exchanger Tubes due to Heavy Hydrocarbon Droplets Impingement. Issue 7 (24th May 2017) - Verhees, Pieter; Mahulkar, Amit V.; Van Geem, Kevin M.; Heynderickx, Geraldine J.
ABSTRACT: This work discusses fouling in the vapor–steam mixture overheater in the convection section of an industrial steam cracker due to the thermal degradation of heavy hydrocarbon droplets deposited on the tube wall. A spray of heavy hydrocarbon multicomponent droplets is injected in a tube of the vapor–steam mixture overheater and the path of the droplets through the tube is followed by an Eulerian–Lagrangian computational fluid dynamics simulation. To study tube fouling, the droplet impingement behavior on the wall, the evaporation of the deposited liquid, and a coking model describing thermal coke formation due to degradation of heavy hydrocarbons are required. To describe the droplet impingement behavior, a regime map for single component millimeter-sized droplets is taken from the literature. Two simulations are performed to study fouling problems in a vapor-mixture overheater tube. Simulation results are found to be grid sensitive. By analyzing and comparing simulation results it is concluded that reliable fouling data require a regime map for the impingement of multicomponent heavy hydrocarbon micron-sized droplets.